Osteogenic differentiation of mesenchymal stem cells with silica-coated gold nanoparticles for bone tissue engineering - Gandhimathi, Chinnasamy (2020)
Multifunctional nanofibrous scaffolds for effective bone tissue engineering (BTE) application must incorporate factors to promote neovascularization and tissue regeneration. In this study, silica-coated gold nanoparticles Au(SiO2) were tested for their ability to promote differentiation of human mesenchymal stem cells (hMSCs) into osteoblasts. Biocompatible poly-ε-caprolactone (PCL), PCL/silk fibroin (SF) and PCL/SF/Au(SiO2) loaded nanofibrous scaffolds were first fabricated by an electrospinning method. Electrospun nanofibrous scaffolds were characterized for fiber architecture, porosity, pore size distribution, fiber wettability and the relevant mechanical properties using field emission scanning electron microscopy (FESEM), porosimetry, determination of water contact angle, measurements by a surface analyzer and tabletop tensile-tester measurements. FESEM images of the scaffolds revealed beadless, porous, uniform fibers with diameters in the range of 164 ± 18.65 nm to 215 ± 32.12 nm and porosity of around 88-92% and pore size distribution around 1.45-2.35 µm. Following hMSCs were cultured on the composite scaffolds. Cell-scaffold interaction, morphology and proliferation of were analyzed by FESEM analysis, MTS (3-(4,5-dimethyl thiazol-2-yl)-5-(3-carboxymethoxyphenyl)-2-(4-sulfophenyl)-2H-tetrazolium inner salt) and CMFDA (5-choromethyl fluorescein acetate) dye assays. Osteogenic differentiation of MSCs into osteogenic cells were determined by alkaline phosphatase (ALP) activity, mineralization by alizarin red S (ARS) staining and osteocalcin expression by immunofluorescence staining. The results revealed that the addition of SF and Au(SiO2) to PCL scaffolds enhanced the mechanical strength, interconnecting porous structure and surface roughness of the scaffolds. This, in turn, led to successful osteogenic differentiation of hMSCs with improved cell adhesion, proliferation, differentiation, mineralization and expression of pro-osteogenic cellular proteins. This provides huge support for Au(SiO2) as a suitable material in BTE.